Removal of Fluoride from Aqueous Solution Using Biomass-Based Adsorbents: A Review - Aryal, Ram Lochan; Poudel, Bhoj Raj; Gautam, Surendra K; Paudyal, Hari; Ghimire, Kedar Nath; Pokhrel, Megh Raj (Journal of Nepal Chemical Society, 2019)
Various separation techniques have been successful for the removal of fluoride from aqueous solution. In this review, an extensive list of various biomass-based adsorbents from literature has been explored and their adsorption capacities under different conditions for the removal of fluoride available in the literature to date are presented. Several adsorbents have shown good adsorption capacities; however, modified biomass had shown excellent adsorption capacities compared to commercial materials. This paper reviews the fluoride uptake capacities of biomass materials and their modified forms as adsorbents against different experimental limits.